Analysis of Financial Management at the Muhamamdiyah Mosque in the Wajo Religion of South Sulawesi, Indonesia - Suarni, Agusdiwana; Nurlina,; Andi Musdalifah Adhe Putri, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The focus of the research is on the treasurers of 14 mosques or mosques owned by Muhammadiyah in Wajo Regency. This study concludes that Muhammadiyah Mosques in Wajo Regency practice the principles of accountability and transparency in their financial management systems, including the receipt and disbursement of mosque funds. Muhammadiyah Mosques in Wajo Regency apply transparency directly to their congregations and the community, usually on Fridays before Friday prayers. Muhammadiyah Mosques in Wajo Regency maintain their accountability by manually recording funds in the financial recording and reporting system, the mosque financial report book. The use of mosque funds is based on two interests, namely internal needs and external needs, such as worship needs such as operational development and building renovation.